1,1′,2,2′-Tetramethyl-3,3′-(4-methoxybenzylidene)di-1H-indole - Cai-Li Zhang; Ping-Ping Ye; Zhi-Qiang Du (Acta Crystallographica Section E, 2009)
The title compound, C28H28N2O, was prepared by condensation of 1,2-bimethylindole and 4-methoxybenzaldehyde. In the molecular structure, the plane of the non-fused benzene ring is twisted with respect to the planes of the two indole ring systems, exhibiting dihedral angles of 72.04 (7) and 72.24 (7)°, while the planes of the two indole ring systems are oriented at a dihedral angle of 87.05 (5)°. Neither hydrogen bonding nor π–π stacking is observed in the crystal structure.